Our governement as influenced by some of our social classes - Morse, Theodore Wattles (My University, 1895)
Introduction: In our country the persons and institution through which the affairs of state are administered stand in close relation to the people. The expression “a government of the people” is more or less significant depending upon what part of the people we have in mind but however the ____ may vary it is certain that a relation, subjective or objective or both, can always be found between a government and its citizens or subjects. There have been times and governments when this relation was not so apparent where for long periods of time the complexion of the nation was given by a few who stood nearest the hand that held the ____, where only after extended intervals of oppression did this vital relation, this interdependency show itself either in wreck or revolt. France has furnished good illustrations of both cases.
Citation: Morse, Theodore Wattles. Our governement as influenced by some of our social classes. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Political science; Government; Theses; Manuscripts (documents)